A stomatal ozone flux–response relationship to assess ozone-induced yield loss of winter wheat in subtropical China - Feng, Zhaozhong; Tang, Haoye; Uddling, Johan; Pleijel, Håkan; Kobayashi, Kazuhiko; Zhu, Jianguo; Oue, Hiroki; Guo, Wenshan (Environmental pollution (1987), 2012)
Stomatal ozone flux and flux–response relationships were derived for winter wheat (Triticum aestivum L.) grown under fully open-air ozone fumigation. A stomatal conductance (gsto) model developed for wheat in Europe was re-parameterized. Compared to European model parameterizations, the main changes were that the VPD and radiation response functions were made less and more restrictive, respectively, and that the temperature function was omitted. The re-parameterized gsto model performed well with an r2 value of 0.76. The slope and intercept of the regression between observed and predicted gsto were not significantly different from 1 to 0, respectively. An ozone uptake threshold of 12 nmol m−2 s−1 was judged most reasonable for the wheat flux–response relationship in subtropical China. Judging from both flux- and concentration-based relationships, the cultivars investigated seem to be more sensitive to ozone than European cultivars. The new flux–response relationship can be applied to ozone risk assessment in subtropical regions. ► Stomatal conductance model was re-parameterized on the basis of LRTAP. ► VPD was less restrictive to stomatal conductance compared to that in European model. ► An ozone uptake threshold of 12 nmol m−2 s−1 was suggested in subtropical regions. ► Ozone flux–response relationship for wheat was derived in sub-tropical China. Stomatal ozone flux–response relationships were derived for winter wheat in subtropical China.